Treatment of Hot Wash Liquor using Fly Ash - Selvaraju Sivamani; Mutharasu Kavya; Vignesh Vinusha (Tropical Aquatic and Soil Pollution, 2022)
Textile industries are the second largest water-consuming industries, next to agriculture. This research is aimed at investigating the utilization of fly ash as a low-cost adsorbent to treat hot wash liquor by employing one factor at a time. Contact time, effluent dosage, pH, mass of adsorbent, temperature, particle size, and agitation speed have been varied to find the optimum conditions for dye removal from hot wash liquor by fly ash. The results from the sorption process show that the maximum dye removal of 56.07% has been obtained at a time of 5 min, an effluent to water ratio of 9:1, pH of 11, an adsorbent dosage of 0.55 g/mL, a temperature of 27 °C, a fly ash particle size of 128 m and an agitation speed of 100 rpm. The analysis of the results was performed through adsorption capacity and percentage colour removal. Hence, the results suggested that fly ash could be used as an effective adsorbent for treating dyehouse effluents.